Immobilizing Zwitterionic Molecular Brush in Functional Organic Interfacial Layers for Ultra-Stable Zn-Ion Batteries - Sun, Limeng; Cao, Xianjun; Gao, Li; Li, Jiayi; Qian, Chen; Wu, Jinhu; Nie, Xinming; Gao, Hong; Huang, Peng; Zhao, Yufei; Wang, Yong; Zhang, Jinqiang; et al. (Nano-Micro Letters, 2025)
Rechargeable zinc-ion batteries have emerged as one of the most promising candidates for large-scale energy storage applications due to their high safety and low cost. However, the use of Zn metal in batteries suffers from many severe issues, including dendrite growth and parasitic reactions, which often lead to short cycle lives. Herein, we propose the construction of functional organic interfacial layers (OIL) on the Zn metal anodes to address these challenges. Through a well-designed organic-assist pre-construction process, a densely packed artificial layer featuring the immobilized zwitterionic molecular brush can be constructed, which can not only efficiently facilitate the smooth Zn plating and stripping, but also introduce a stable environment for battery reactions. Through density functional theory calculations and experimental characterizations, we verify that the immobilized organic propane sulfonate on Zn anodes can significantly lower the energy barrier and increase the kinetics of Zn2+ transport. Thus, the Zn metal anode with the functional OIL can significantly improve the cycle life of the symmetric cell to over 3500 h stable operation. When paired with the H2V3O8 cathode, the aqueous Zn-ion full cells can be continuously cycled over 7000 cycles, marking an important milestone for Zn anode development for potential industrial applications. Highlights: 1 An organic-assisted solid electrolyte interface pre-construction creates a functional organic interfacial layer (OIL-IPS@Zn) with aligned zwitterionic structures, suppressing side reactions and enhancing Zn2+ transport. 2 OIL-IPS@Zn shows superior electrolyte affinity, enabling symmetric cells to operate stably for 3500 h at 1 mA cm−2/1 mAh cm−2 and 3200 h at 50 mA cm−2/10 mAh cm−2. 3 With 99.90% Zn plating/stripping efficiency, full cells paired with H2V3O8 cathodes achieve over 7000 cycles.